PERAN KOMITE SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN PENDIDIKAN DI SEKOLAH DASAR SWASTA SUSTER KECAMATAN SINGKAWANG BARAT - Nono, Irena; Sukmawati, Sukmawati; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractÂ The school program has planned and implemented so that the effectiveness of education services is achieved as expected. Achieving school goals through the program cannot be achieved effectively, if the school only hopes for the government and the foundation. The Schools need partners to achieve effective service in education. The school partner is the school committee as a forum for the community to support the school in carrying out its program.The Role of School Committees in Increasing the Effectiveness of Education Services in the Suster Private Elementary School, West Singkawang Sub-Districtwith a focus on research : 1) The role of school Committees in providing Advisory Agencies, 2) Support (Supporting Agency), 3) The roles as a controlling agency, 4) As school Committee as an intermediary between the government and the community (Mediator Agency), 5) The factors influence the role of the School Committee in increasing the effectiveness of education services. The results of the study concluded in general the Suster Private Elementary School, West Singkawang Sub-District, School Committee could be categorized as good. In particular, the role of the School Committee has carried out roles as: 1) Advisory Agency, 2), Sopporting Agency, 3) Controlling Agency, 4) The intermediary between the government and the community (Mediator Agency), it's good even though there are still some inputs and suggestions from researchers. Â Keywords: Advisory Agency, Controlling Agency, Mediator Agency, and Supporting Agency